6-4(y+3)=2(y-1)

Simple and best practice solution for 6-4(y+3)=2(y-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-4(y+3)=2(y-1) equation:



6-4(y+3)=2(y-1)
We move all terms to the left:
6-4(y+3)-(2(y-1))=0
We multiply parentheses
-4y-(2(y-1))-12+6=0
We calculate terms in parentheses: -(2(y-1)), so:
2(y-1)
We multiply parentheses
2y-2
Back to the equation:
-(2y-2)
We add all the numbers together, and all the variables
-4y-(2y-2)-6=0
We get rid of parentheses
-4y-2y+2-6=0
We add all the numbers together, and all the variables
-6y-4=0
We move all terms containing y to the left, all other terms to the right
-6y=4
y=4/-6
y=-2/3

See similar equations:

| 3x+24=-15 | | x112.5(x+4)=4.75 | | -6(6b-8)=11+b | | 12/7n=180 | | 6n+4=10n-20 | | 12(x−360)=12012(x−360)=120 | | 10x+15-7x-6=0 | | 14x+1=13+8x | | 24(x-200)=30800 | | -5x=-25x-11 | | 5b-4b=6b+12 | | 6x^2+16x=687 | | 2(4x–9)= | | 60=95x | | 2(4x–9)=16–3x | | 3x-3(-4x-7)=-27+7x | | 0.6x-1.1=-7.7 | | 15/2=15/4r+5/4r | | 0.375x-19=17 | | 28x-16-7x=12 | | 1+5a+2a=15 | | 2x+6-5=5x+13 | | 118=x^2-2x | | -5x-5-6=4 | | 216^(3x)*216^(x)=36^(3x+2) | | 5^(1-8x)=(4^x) | | 4.4−1.9=8.3n−7.3n−8.7 | | 3/8x-19=17 | | 100=4t+90 | | 5^1-8x=4x | | X2+y2=121 | | 2x-18=18-x |

Equations solver categories